PENGEMBANGAN INDUSTRI KALIGRAFI: PELUANG DAN TANTANGAN MENINGKATKAN EKONOMI UMAT ISLAM - Rozi Sakhbana Hasibuan (Yayasan Haiah Nusratul Islam, 2024)
The Islamic calligraphy industry has great potential to improve the economy of Muslims through various forms of commercialization and cultural preservation. The main opportunities include the art and collection market, education and training, as well as the development of creative industries with the application of calligraphy to design and digitalization products. Apart from that, cultural and religious tourism that utilizes calligraphy can attract tourists and improve the local economy. However, the industry faces challenges such as lack of financial support, difficulties in accessing global markets, copyright protection issues, and a lack of adequate education and training. Strategies to overcome these challenges include increased financial support, stronger copyright protection, better education and training, and the use of digital technology. With the right approach, the calligraphy industry can develop rapidly and contribute significantly to the Muslim economy.